Estudio ultrasonográfico de los órganos abdominales de la chosna (Potos flavus) mantenido en cautiverio (Lima, Perú) - Perales Huaraca, Jacqueline (2020)
The aim of the investigation was to carry out the ultrasonographic evaluation of the abdominal organs of the kinkajou (Potos flavus). The seven adult individuals (2 males and 5 females) from the “Buen Pastor” zoo (Los Olivos, Lima) were evaluated. An ultrasound equipment with a 4-9 MHz convex transducer was used to evaluate the topography, shape, margins, ecotexture, and echogenicity of the abdominal organs. The spleen has a slightly thicker head than the body and tail. The liver showed medium echogenicity, isoechogenic in relation to the kidney and hypoechogenic in relation to the spleen. The right kidney was found slightly more cranial than the left, presented a renal cortex of medium echogenicity, a slightly hyperechogenic medulla in relation to the cortex, and a 2: 1 medullary cortex ratio. The bladder wall presented a heterogeneous ecotexture with poorly defined walls. The ultrasound characteristics of the abdominal organs (liver, gallbladder, bladder and stomach) of P. flavus showed similarity with that described in domestic and wild cats, as well as with the coati (Nasua nasua). However, the spleen and kidney show ultrasound characteristics peculiar of this species. The ultrasound characteristics of the uterus were like those described in N. nasua.